A qualitative study of women living with HIV: understanding their subjective experiences and psycho-social needs - Omar Din, Meriam; Mohamad, Mardiana (s.n, 2012)
In view of the increasing rate of women with HIV and the complex psychological and social impact experienced by these women, there is a need to conduct an in-depth study to understand the issues and needs of these women. This study intends to explore these needs by conducting a qualitative study on HIV infected women living in Kuala Lumpur. Five HIV positive adult women agreed to participate in this study. Three group focused sessions were conducted using the unstructured interview approach allowing free expression of their subjective experiences. The recorded transcripts of the group focused interviews were analyzed to identify unifying themes and common patterns related to their psychological stress and socio-psychological needs of the participants. Overall, the study indicated that majority participants experiences most of the symptoms of anxiety and depression related to their experience living with HIV. The experience of anxiety was mostly expressed as the fear of facing the AIDS stage of their illness. Positive feeling was mainly associated with feeling of gratitude for the available supportive institution and acceptance by family members. Needs for connectedness with existing family members and sense of belongings to a family were expressed frequently by all participants. HIV-related stigma by the community is felt by most participants. Religious approach was mentioned by all participants as a way to accept their condition. However there is a mix expression of complete and partial acceptance of the HIV experience. Future study on the prevalence of depressive symptoms and anxiety among HIV positive women need to be examined. A group therapy approach integrating psychological, religious and health could be further explored.